International Archives Week 2025: #ArchivesAreAccessible – Archives for Everyone - ICA (ICA, 2025)
As archives evolve in the digital age, the ability to provide greater access to archival content is more important than ever. This year’s theme will celebrate how archives around the world are embracing new technologies to open up their collections, making it easier for people to engage with history, culture, and knowledge. Whether through digital platforms, enhanced user interfaces, or innovative preservation techniques, the goal is to ensure that archives are available to all, regardless of geographical location or physical limitations.

ICA Human Rights Archives Directory - HRWG ICA (Human Rights Working Group - International Council on Archives) (Archivists Watch, 2011)
For some years now, the ICA Human Rights Working Group (HRWG) has been trying to establish a directory of human rights archives from around the globe.  This summer, I began volunteering with the IC…
Keywords: References - Comma (2020 1-2), Archives and Human Rights